2005
DOI: 10.14411/eje.2005.109
|View full text |Cite
|
Sign up to set email alerts
|

Natural prey of the jumping spider Menemerus taeniatus (Araneae: Salticidae)

Abstract: Abstract. The natural prey of the jumping spider Menemerus taeniatus (L. Koch, 1867) was studied on the Absheron Peninsula, Azerbaijan. The percentage of specimens of M. taeniatus found feeding was low (10.7%). This investigation showed that M. taeniatus is a polyphagous predator feeding on a wide range of arthropods, including representatives of eight arthropod orders. The primary food of M. taeniatus was Diptera and Lepidoptera, which collectively made up about two thirds of total prey. The length of prey ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Ma et al (2005a) have shown that successive stages of immature Nabis kinbergii prey on P. xylostella at increasing rates, and that the number of prey consumed by N. kinbergii decreased as body size of prey increased. Huseynov (2005) found the most frequent prey taken by salticid spiders were other arthropods with a size of 50 Ð100% of the spiderÕs own body length.…”
Section: Discussionmentioning
confidence: 97%
“…Ma et al (2005a) have shown that successive stages of immature Nabis kinbergii prey on P. xylostella at increasing rates, and that the number of prey consumed by N. kinbergii decreased as body size of prey increased. Huseynov (2005) found the most frequent prey taken by salticid spiders were other arthropods with a size of 50 Ð100% of the spiderÕs own body length.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, Salticidae comprised 88.3% of the total sampled spiders, followed by Atypidae (8.4%). Salticid spiders are polyphagous predators that feed on a wide range of arthropods; the size of prey can reach twofold the size of the spider 90 . The prey–predator interactions have been revealed in various ecosystems 90 92 .…”
Section: Discussionmentioning
confidence: 99%
“…Many adult Lepidoptera (butterflies and moths) are palatable to spiders and occur in a variety of habitats, but are usually not aggregated. They are regularly captured by many euryphagous generalists, both web-building and cursorial species (Bristowe, 1941;Nyffeler & Benz, 1981;Nentwig, 1987;Lockley, Young & Hayes, 1989;Dix & Jennings, 1995;Huseynov, 2005;Yamanoi & Miyashita, 2005). Predominantly lepidopterophagous species are found mainly in the web-building guilds (see online Table S4).…”
Section: (4) Lepidopterophagymentioning
confidence: 99%